Beauty and the Patriarchal Beast: Men and Their Roles in Women Want(h)ing(s) in Colleen Hoover’s It Ends With Us - Riva, Camille Abegail R.; Naidas, Michael S.; Flores, Kathleen B.; Agum, Arjem Noryn C.; Aclan, Eunice M. (8ISC Proceedings: Arts and Education, 2022)
This paper aimed to examine the themes of domestic violence and the roles of men and their treatment of women in a household context, as seen through Colleen Hoover’s bestselling novel It Ends With Us. A descriptive-analytical approach was employed in interpreting the novel’s underpinnings. Elements of the novel were delved through the lenses of Sigmund Freud’s Psychoanalytic approach, Biographical Criticism, and Ainsworth and Bowlby’s Attachment Theory. A thorough analysis of the novel’s elements reflects both the positive (provider and protector) and negative (abuser, controller, and possessor) roles of men and their treatment of women. Furthermore, the novel revealed that women dealt with the treatment they received from men through the following stages: denying the acts of abuse, fathoming the occurrence of abuse, creating an outlet to curtail abuse, and breaking the pattern of abuse. It can be concluded that It Ends With Us echoes the voice of a female author who witnessed domestic violence and reflects the events through a written work. Through this study, contemporary literature is not only viewed as a form of entertainment among young people but also as a reflection of the concealed reality that lies beyond closed doors, not only in the contemporary Philippine culture but anywhere in the world. Keywords : contemporary literature, patriarchy, biographical literature, abusive relationship, domestic violence